All-digital PLL frequency and phase noise degradation measurements using simple on-chip monitoring circuits - Park, Gyusung (2019)
Using simple on-chip monitoring circuits, we precisely characterized the impact of hot carrier injection and bias temperature instability on frequency and phase noise degradation of a 65nm all-digital PLL circuit. Experimental data shows that PLL phase noise degrades with aging even though the output frequency is maintained constant due to the PLL feedback operation. Results show that applying high temperature annealing can recover most of the phase noise degradation.